Porous material rich in nitrogen, oxygen and fluorine heteroatoms and preparation method and application thereof
The porous materials rich in nitrogen, oxygen and fluorine heteroatoms prepared by copolymerizing bisphenol AF and tripercyanochloride solve the problem of high cost and difficult recovery of adsorbents in the recycling of existing lithium-ion batteries, and achieve the effect of efficient adsorption of lithium ions and reducing recovery costs.
Patent Information
- Application Number
- CN202410119595.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-01-29
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-01-29
AI Technical Summary
In the recycling of existing lithium-ion batteries, adsorbents are costly and difficult to recover, and they are prone to dissolution during the lithium-ion elution process, affecting their service life.
Copolymerization of bisphenol AF and tripercyanochloride is used to prepare porous materials rich in nitrogen, oxygen and fluorine heteroatoms. Through Soxhlet extraction and vacuum drying processes, a material that efficiently adsorbs lithium ions is obtained.
It has achieved efficient adsorption of lithium ions in waste liquid recycling of lithium ion batteries, reducing recycling costs, improving the stability and adsorption capacity of materials, and meeting environmental protection and green environment requirements.
Smart Images

Figure CN118022709B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of materials and relates to a dual-template method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms and a preparation method thereof and an application thereof in adsorbing lithium ions. Background Art
[0002] With the continuous development of the new energy field, electric vehicles have gradually become the main body of new energy vehicles, and lithium-ion batteries are the most common power source. Lithium-ion batteries (LIBs) have gradually become the first choice for new energy vehicles due to their high energy density, long-term stable cycle performance, and environmental friendliness. In 2022, China's new energy vehicle production will be 7.058 million, a year-on-year increase of 96.9%. The lithium battery market shipments will be 658GWh, a year-on-year increase of 101%. According to GGII, the annual compound growth rate of China's lithium battery market will reach 53.3% from 2021 to 2025, and China's lithium battery shipments will reach 1,805GWh in 2025. With the continuous expansion of the application scope of lithium-ion batteries, problems such as shortage of lithium resources and lithium-ion battery pollution have emerged. If lithium-ion batteries are not treated, they will not only have a serious impact on the environment, but also cause serious waste of resources. Therefore, with the increasing impact of lithium-ion batteries on the ecological environment and the huge economic value of waste lithium-ion batteries themselves, lithium-ion battery recycling has become an emerging industry. Using high-performance materials to recycle lithium ions can not only alleviate environmental pressure, but also recycle valuable lithium ions and alleviate the pressure of lithium resource shortage.
[0003] Adsorption is an environmentally friendly separation method. How to separate lithium from waste liquid containing lithium ions is a difficult problem in the lithium-ion battery processing process. If a material is invented that can adsorb lithium from waste liquid containing lithium ions, and the adsorbent can be reused, it will greatly save costs, reduce wastewater discharge, and generate economic and environmental benefits.
[0004] In short, synthesize efficient porous materials, adsorb lithium ions, reuse the adsorbed-desorbed lithium ions, recycle the lithium in lithium-ion batteries, protect the environment, and generate economic and social benefits. However, the lithium ion adsorbents in the prior art have the disadvantages of high cost and difficulty in recycling. The adsorbents currently used in adsorption lithium extraction technology mainly include aluminum salt adsorbents and ion sieve adsorbents, but these two types of adsorbents have complex processes and high costs. At the same time, in the process of eluting lithium ions, some Mn 4+ A disproportionation reaction will occur to convert Mn 2+ Entering the water phase, the manganese ion sieve will dissolve during use, thus affecting its service life. Summary of the invention
[0005] The present invention uses a convenient method to synthesize a porous material rich in nitrogen, oxygen, and fluorine heteroatoms, adsorb lithium ions in power battery waste liquid, reduce the cost of lithium ion recovery, and achieve the goal of turning waste into treasure and reducing pollution emissions. Therefore, it meets the requirements of environmental protection and green environment. It can be expected that the material will be widely used in future industrial production.
[0006] The technical solution provided by the present invention is as follows:
[0007] The present invention copolymerizes bisphenol AF and cyanuric chloride to generate a porous material rich in nitrogen, oxygen and fluorine atoms. The porous material is used to adsorb lithium ions in waste liquid recovered from power batteries, thereby reducing the cost of lithium ion recovery and achieving the goal of turning waste into treasure and reducing pollution emissions.
[0008] The specific technical solutions are as follows:
[0009] A method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms comprises the following steps: using dichloromethane as a solvent, polystyrene as an organic template and potassium carbonate as an inorganic template, heating and polycondensing dichloromethane, polystyrene, potassium carbonate, anhydrous sodium sulfate, cyanuric chloride and bisphenol AF, performing two Soxhlet extractions to respectively remove polystyrene, cyanuric chloride and bisphenol AF, and vacuum drying to obtain a porous material rich in nitrogen, oxygen and fluorine heteroatoms.
[0010] Furthermore, the molar ratio of cyanuric chloride to bisphenol AF is 1.9:2.2-3.
[0011] The molar ratio of dichloromethane to cyanuric chloride is 117 to 351:2;
[0012] The mass ratio of polystyrene to cyanuric chloride is 50-200:74;
[0013] The molar ratio of potassium carbonate to cyanuric chloride is 7 to 29:4;
[0014] The molar ratio of anhydrous sodium sulfate to cyanuric chloride is 1 to 9:1;
[0015] Furthermore, the heating polycondensation time is 5 to 8 hours; the heating polycondensation temperature is 160 to 198°C.
[0016] Furthermore, the solvent used in the first Soxhlet extraction is dichloromethane, the extraction time is 22 to 28 hours, and the extraction temperature is 35 to 40°C.
[0017] Furthermore, the solvent used in the second Soxhlet extraction is ethanol, the extraction time is 18-20 hours, and the extraction temperature is 78-80°C.
[0018] Furthermore, the vacuum drying temperature is 85 to 95° C., and the time is 2 to 3 hours.
[0019] The preparation method of a porous material rich in nitrogen, oxygen and fluorine heteroatoms includes: step 1. using dichloromethane as a solvent, polystyrene as an organic template, potassium carbonate as an inorganic template, adding anhydrous sodium sulfate, cyanuric chloride and bisphenol AF, heating and polycondensing, performing two Soxhlet extractions to remove polystyrene, cyanuric chloride and bisphenol AF respectively, and vacuum drying to obtain a porous material rich in nitrogen, oxygen and fluorine heteroatoms.
[0020] Step 2: Place the porous material into a solution containing lithium ions to adsorb the lithium ions.
[0021] Wherein: in step 1, the molar ratio of cyanuric chloride to bisphenol AF is 1.9:2.2-3; when the molar ratio is less than 1.9:3 or greater than 2.2:3, the yield is significantly reduced, and the physical properties of the material are reduced. The heating polycondensation time is 5-8 hours. When the time is less than 5 hours, the reaction yield is reduced. When the yield is greater than 8 hours, the yield is not significantly improved. The heating temperature is 160-198°C. When the temperature is lower than 160°C, the reaction time becomes longer; finally, the ethanol Soxhlet extraction time is 18-20 hours. When the time is less than 18 hours, the impurity removal is incomplete and the yield is low. When the time is greater than 20 hours, there is no significant improvement. The second Soxhlet extraction temperature is 78-80°C, the boiling point of ethanol. In step 2, the mass ratio of adsorbent material to lithium ions is 6-10:1. When the ratio is less than 6:1, the adsorption is incomplete; when the ratio is greater than 10:1, the concentration of residual lithium ions is not significantly reduced.
[0022] The present invention also provides a porous material rich in nitrogen, oxygen and fluorine heteroatoms, which is prepared by the above method.
[0023] The present invention also provides the use of the above-mentioned porous material rich in nitrogen, oxygen and fluorine heteroatoms in adsorbing lithium ions in power battery waste liquid recovery.
[0024] Furthermore, the mass ratio of the porous material to lithium ions is 6 to 10:1.
[0025] Beneficial Effects
[0026] Lithium ions are easily adsorbed in porous materials by electrostatic attraction with N, O, and F atoms with greater electronegativity in organic materials. The present invention provides a porous material that efficiently adsorbs lithium ions. The raw materials are green and economical, and the performance is stable. Compared with manganese-based ion sieves, the stability is improved by 12% after 10 regeneration cycles; it can efficiently adsorb lithium ions in power battery waste liquid. Compared with inorganic adsorbents, the adsorption capacity of lithium ions in this material is increased by 16%, reducing the cost of lithium ion recovery, and achieving the goal of turning waste into treasure and reducing pollution emissions. Therefore, it meets the requirements of environmental protection and green environment, and produces economic and social benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1The invention relates to a preparation route of a porous material rich in nitrogen, oxygen and fluorine heteroatoms.
[0028] Figure 2 It is the infrared spectrum of cyanuric chloride, bisphenol AF and new porous materials.
[0029] Figure 3 It is a TEM photo of a porous material rich in nitrogen, oxygen and fluorine heteroatoms. Figures af refer to the structure of the same sample at the same position at different magnifications. Figure a refers to the structure of the porous material provided by the present invention at a magnification of 500nm; Figure b refers to the structure of the porous material provided by the present invention at a magnification of 200nm; Figure c refers to the structure of the porous material provided by the present invention at a magnification of 100nm; Figure d refers to the structure of the porous material provided by the present invention at a magnification of 20nm; Figure d refers to the structure of the porous material provided by the present invention at a magnification of 10nm; Figure f refers to the structure of the porous material provided by the present invention at a magnification of 5nm. DETAILED DESCRIPTION
[0030] like Figure 1 As shown, in order to prepare a porous material rich in nitrogen, oxygen, and fluorine heteroatoms, polystyrene is used as a template, added to dichloromethane and stirred to form a linear structure in the solution, and then cyanuric chloride and bisphenol AF are added to the reaction mixture. π-π stacking interactions occur between the benzene rings on polystyrene and the benzene rings on bisphenol AF and the triazine rings on cyanuric chloride. Therefore, bisphenol AF can approach and react with cyanuric chloride 2,4,6-trichloro-1,3,5-triazine to form ethers. The porous material synthesized using the organic template polymer polystyrene and the inorganic template potassium carbonate and sodium sulfate contains three atoms containing lone electron pairs, namely N, O, and F, which bind to lithium ions through lone electron pairs and adsorb lithium ions.
[0031] like Figure 2 As shown, in the product - a porous material rich in nitrogen, oxygen, and fluorine heteroatoms, 1495 cm -1 The peak at 1509 cm is the characteristic absorption peak of the triazine ring in cyanuric chloride, corresponding to the porous material. -1 The triazine ring absorption peak at 1620cm -1 With 1518cm -1 It is the characteristic absorption peak of the benzene ring in bisphenol AF, corresponding to the absorption peak of the benzene ring at 1569cm-1 in porous materials; 1235cm -1 With 1170cm -1 is the absorption peak of COC in the porous material, which indicates the formation of ether bonds. In short, the triazine ring is connected to the benzene ring on bisphenol AF by an ether bond. The above data show that the reactant cyanuric chloride and bisphenol AF undergo a polymerization reaction, and the product is a porous material rich in nitrogen, oxygen, and fluorine heteroatoms.
[0032] like Figure 3 As shown in the figure, the surface morphology of a porous material rich in nitrogen, oxygen, and fluorine atoms was characterized by TEM. As can be seen from the photo, the new porous material contains clearly visible mesopores ( Figure 3 -d, e, f). This is because dual templates were used during the synthesis, leaving pores after washing them away.
[0033] Example 1.
[0034] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0035] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0036] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene, and then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0037] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.405 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 76.5%.
[0038] Example 2.
[0039] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.70 g, 3.81 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0040] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0041] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0042] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.356 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 70.1%.
[0043] Example 3.
[0044] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.81 g, 4.41 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0045] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0046] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0047] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.402 g) was obtained, which was a porous material rich in nitrogen, oxygen and fluorine heteroatoms. The yield was 75.9%.
[0048] From Examples 1-3, it can be seen that when the molar ratio of cyanuric chloride to bisphenol AF is 1.9-2.2:3, the reaction yield is relatively high. The molar ratio of cyanuric chloride to bisphenol AF is 2:3, which is further described in the examples.
[0049] Example 4.
[0050] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0051] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 160°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0052] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0053] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.403 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 76.1%.
[0054] Example 5.
[0055] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0056] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 198°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0057] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0058] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.405 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 76.5%.
[0059] From Examples 1, 4 and 5, it can be seen that when the reaction temperature is between 160 and 198° C., the reaction yield is stable. This will be further described in the examples at 180° C.
[0060] Example 6.
[0061] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0062] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 8 hours, and the heating was stopped.
[0063] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0064] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.403 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 76.1%.
[0065] Example 7.
[0066] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0067] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 6.5 hours, and the heating was stopped.
[0068] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 19 hours to remove cyanuric chloride and bisphenol AF.
[0069] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.405 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 76.5%.
[0070] From Examples 1, 6 and 7, it can be seen that when the reaction time is 5-8 hours, the reaction yield is stable. This will be further described in the examples based on 5 hours.
[0071] Example 8.
[0072] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0073] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0074] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 18 hours to remove cyanuric chloride and bisphenol AF.
[0075] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.402 g) was obtained, which was a porous material rich in nitrogen, oxygen and fluorine heteroatoms. The yield was 75.9%.
[0076] Example 9.
[0077] (1) Take polystyrene (2.00 g) and add it to a beaker. Then add dichloromethane (15.00 mL) and stir at room temperature for 1 hour to dissolve it completely. Take cyanuric chloride (0.74 g, 4.01 mmol), bisphenol AF (2.02 g, 6.01 mmol), potassium carbonate (2.82 g, 20.40 mmol), and anhydrous sodium sulfate (0.96 g, 6.75 mmol) and add them to the above solution. Stir thoroughly at room temperature for 1 hour.
[0078] (2) The solvent was slowly evaporated at 30°C, and the remaining mixed solid was placed in a quartz boat, placed in a tube furnace, and slowly heated to 180°C. The reaction was carried out for 5 hours, and the heating was stopped.
[0079] (3) The product was dissolved in dichloromethane and extracted with dichloromethane for 24 hours to remove polystyrene. The product was then extracted with ethanol solution for 20 hours to remove cyanuric chloride and bisphenol AF.
[0080] (4) After vacuum drying at 90°C for 2.5 hours, a white solid (0.401 g) of a porous material rich in nitrogen, oxygen and fluorine atoms was obtained with a yield of 75.7%.
[0081] From Examples 1, 8 and 9, it can be seen that when the second Soxhlet extraction time is 18-20 hours, the reaction yield increases first and then decreases. This will be further described in the examples according to 19 hours.
[0082] Material properties experiment:
[0083] Example 10.
[0084] Take the porous material prepared in Example 1 (7.5 mg), add lithium ion aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy to be 5.25 ppm and the adsorption rate is 79.01%.
[0085] Example 11.
[0086] Take the porous material prepared in Example 1 (10 mg), add lithium ion aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy to be 0.71 ppm and the adsorption rate is 97.15%.
[0087] Example 12.
[0088] Take the porous material prepared in Example 1 (12.5 mg), add lithium chloride lithium ion aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy to be 0.76 ppm and the adsorption rate is 96.96%.
[0089] It can be seen from Examples 10, 11, and 12 that the mass ratio of the adsorption material to the lithium ions is 6 to 10:1. When the ratio is less than 6:1, the adsorption rate is low; when the ratio is greater than 10:1, the concentration of the remaining lithium ions is not significantly reduced.
[0090] Example 13.
[0091] Take the porous material prepared in Example 1 (10 mg), add lithium chloride aqueous solution (pH = 12.5, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy to be 0.29 ppm and the adsorption rate to be 98.85%. Example 14.
[0092] Take the porous material prepared in Example 1 (10 mg), add lithium chloride aqueous solution (pH = 10, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy to be 3.92 ppm and the adsorption rate to be 84.31%.
[0093] From Examples 11, 13, and 14, it can be seen that when the adsorption pH is in the range of 10-12, the adsorption rate is stable. When pH ≤ 10, the adsorption rate is significantly reduced; when pH > 12, the adsorption rate is slightly improved. This will be further described in the examples according to pH = 12.
[0094] Example 15.
[0095] Take the porous material (10 mg) prepared in Example 1, add lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the remaining lithium ion concentration by atomic absorption spectrometry. The solution is filtered to obtain a solid, dried, desorbed with HCl (0.6 mol / L, 100 mL) solution for 1 hour, filtered to obtain a solid, dried, added lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stirred at room temperature for 1 hour, filtered, and determined the remaining lithium ion concentration by atomic absorption spectrometry. Repeat the above steps 10 times. After 10 cycles of testing, the adsorption capacity of the porous material for lithium ions is 90% of the initial adsorption capacity.
[0096] Example 16.
[0097] Take MnO (10 mg), add lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the remaining lithium ion concentration by atomic absorption spectrometry. The solution is filtered to obtain a solid, dried, desorbed with pure water (100 mL) for 1 hour, filtered to obtain a solid, dried, added lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stirred at room temperature for 1 hour, filtered, and the remaining lithium ion concentration was determined by atomic absorption spectrometry. The above steps were repeated 10 times. After 10 cycles of testing, the adsorption capacity of the porous material for lithium ions was 70% of the initial adsorption capacity.
[0098] Example 17.
[0099] Take MnO 2 (10 mg), add lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the remaining lithium ion concentration by atomic absorption spectrometry. The solution is filtered to obtain a solid, dried, desorbed with pure water (100 mL) for 1 hour, filtered to obtain a solid, dried, added lithium chloride aqueous solution (pH = 12, 25 mg / L, 50 mL), stirred at room temperature for 1 hour, filtered, and the remaining lithium ion concentration was determined by atomic absorption spectrometry. The above steps were repeated 10 times. After 10 cycles of testing, the adsorption capacity of the porous material for lithium ions was 80% of the initial adsorption capacity.
[0100] It can be seen from Examples 15, 16 and 17 that the porous material provided by the present invention has a 12% higher stability after 10 regeneration cycles compared to the manganese-based adsorbent.
[0101] Example 18.
[0102] Take the porous material prepared in Example 1 (10 mg), add lithium chloride aqueous solution (pH = 10, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the residual lithium ion concentration by atomic absorption spectroscopy. The adsorption capacity of the porous material for lithium ions is calculated to be 17.4 mg / g.
[0103] Example 19.
[0104] Take Al(OH) 3 (10 mg), add lithium chloride aqueous solution (pH = 10, 25 mg / L, 50 mL), stir at room temperature for 1 h, filter, and measure the remaining lithium ion concentration by atomic absorption spectroscopy to calculate Al(OH) 3 The adsorption capacity for lithium ions is 15.06 mg / g.
[0105] Example 20.
[0106] Take AlCl 3 (10 mg), add lithium chloride aqueous solution (pH = 10, 25 mg / L, 50 mL), stir at room temperature for 1 hour, filter, and determine the remaining lithium ion concentration by atomic absorption spectrometry to calculate AlCl 3 The adsorption capacity for lithium ions is 9.1 mg / g.
[0107] It can be seen from Examples 18, 19 and 20 that the porous material provided by the present invention has an adsorption capacity for lithium ions increased by 16% compared to inorganic adsorbents.
Claims
1. A method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms, characterized in that: The preparation method comprises the following steps: using dichloromethane as a solvent, polystyrene as an organic template, and potassium carbonate as an inorganic template, fully stirring dichloromethane, polystyrene, potassium carbonate, anhydrous sodium sulfate, cyanuric chloride and bisphenol AF, heating for polycondensation, performing two Soxhlet extractions to remove polystyrene, cyanuric chloride and bisphenol AF respectively, and vacuum drying to obtain a porous material rich in nitrogen, oxygen and fluorine heteroatoms; The molar ratio of cyanuric chloride to bisphenol AF is 1.9:2.2~3; the molar ratio of dichloromethane to cyanuric chloride is 117~351:2; the mass ratio of polystyrene to cyanuric chloride is 50~200:74; the molar ratio of potassium carbonate to cyanuric chloride is 7~29:4; the molar ratio of anhydrous sodium sulfate to cyanuric chloride is 1~9:
1.
2. The method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms according to claim 1, characterized in that: The heating polycondensation time is 5 to 8 hours; the heating polycondensation temperature is 160 to 198°C.
3. The method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms according to claim 1, characterized in that: The solvent used in the first Soxhlet extraction is dichloromethane, the extraction time is 22 to 28 hours, and the extraction temperature is 35 to 40°C.
4. The method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms according to claim 1, characterized in that: The second Soxhlet extraction uses ethanol as the solvent, takes 18-20 hours, and the extraction temperature is 78-80°C.
5. The method for preparing a porous material rich in nitrogen, oxygen and fluorine heteroatoms according to claim 1, characterized in that: The vacuum drying temperature is 85~95℃ and the time is 2~3 hours.
6. A porous material rich in nitrogen, oxygen and fluorine heteroatoms, characterized in that: Prepared by the method according to any one of claims 1 to 5.
7. Use of the porous material rich in nitrogen, oxygen and fluorine heteroatoms as described in claim 6 in adsorbing lithium ions in power battery waste liquid recovery.
8. The use according to claim 7, characterized in that: The mass ratio of the porous material to lithium ions is 6 to 10:1.
Citation Information
Patent Citations
Preparation method of amino group-containing porous material, and application of amino group-containing porous material in recover of waste electric appliance precious metals
CN104910379A
Oxygen reduction catalyst containing fluorine, nitrogen and carbon elements and preparation method thereof
CN107134581A